Reference values, intrarater reliability, and measurement error for the closed kinetic chain upper extremity stability test and upper quarter y balance test in young adults - Anna Luiza Teixeira; Anamaria Siriani de Oliveira; Nathália Alves Rodrigues; Guilherme Augusto Santos Bueno; Maria Eduarda Oliveira Novais; Rayanne de Paula Moreira; Thiago Vilela Lemos; João Paulo Chieregato Matheus; José Roberto de Souza Júnior (Universidade Estadual Paulista (UNESP), 2021)
Abstract Aims: To describe reference values for the Closed Kinetic Chain Upper Extremity Stability Test (CKCUEST) and Upper Quarter Y Balance Test (UQYBT) in young adults, and to determine whether there were differences in both tests based on gender and age. Intrarater reliability and measurement error were also assessed. Methods: Test-retest design with a sample of 146 young adults. The CKCUEST (number of touches, normalized score, and power) and the UQYBT (normalized reach in the medial, superolateral, and inferolateral direction, and the composite score) were used. Mean and standard deviation were calculated for both tests. A linear and a mixed regression model were applied to determine significant differences in test scores. Reliability was determined using Intraclass Correlation Coefficient (ICC) and error measurement through Standard Error of Measurement (SEM) and Smallest Detectable Change (SDC). Results: Normative values were established and divided by gender and age. Men presented greater scores regarding the number of touches, power score, superolateral and inferolateral reaches. Good intrarater reliability was found for both tests. In the CKCUEST, the SEM and SDC values were 1 and 3 touches. In the UQYBT, the SEM values ranged from 3 to 7 cm, while the SDC ranged from 8 to 19 cm. Conclusion: Normative data were provided and men presented greater scores than women. Good intrarater reliability was found and values of SEM and SDC were established. Clinicians must use both tests in clinical practice since different aspects of the upper quarter are assessed.